2018
DOI: 10.1159/000491642
|View full text |Cite
|
Sign up to set email alerts
|

The Optimal Timing of Restaging Resection before Introduction of Bacillus Calmette-Guerin Immunotherapy in Patients with High-Risk Non-Muscle-Invasive Bladder Cancer

Abstract: Introduction: The study aimed to analyze the influence of restaging transurethral resection of bladder tumor (reTURB) timing on outcomes in patients receiving Bacillus Calmette-Guerin (BCG) immunotherapy. Material and Methods: This retrospective study enrolled 491 patients with bladder cancer receiving BCG intravesical therapy between 1998 and 2016. All patients were followed up for at least 12 months and received at least 7 BCG instillations. The patients were analyzed in terms of recurrence free, progression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 15 publications
1
16
1
Order By: Relevance
“…Nevertheless, our analyses might have underestimated the effect of SLR and similar outcomes in the assessed groups indicate that the patient group subjected to a SLR is associated with worse prognosis and that the SLR per se could be pushing these estimates towards unity. Delayed time to SLR has been proposed to decrease RFS and PFS, if the SLR is performed 6 or 8 wk, respectively, after the primary resection [7,19]. However, as opposed to previous reports, the present study showed no association with time to SLR.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, our analyses might have underestimated the effect of SLR and similar outcomes in the assessed groups indicate that the patient group subjected to a SLR is associated with worse prognosis and that the SLR per se could be pushing these estimates towards unity. Delayed time to SLR has been proposed to decrease RFS and PFS, if the SLR is performed 6 or 8 wk, respectively, after the primary resection [7,19]. However, as opposed to previous reports, the present study showed no association with time to SLR.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, the effect-size for the SLRintervention in that study on both RFS and PFS is larger than the expected differences for those outcome measures between adjuvant instillations with mitomycin and BCG [4]. The remaining evidence for SLR emanates from retrospective data hampered by studying heterogeneous cohorts, being influenced by selection bias, and also showing conflicting results [5][6][7][8][9][10]. However, some of the series included in that evaluation did not use adjuvant BCG instillations, or even no adjuvant instillations at all, and the largest study assessed did not report progression-free survival, the most important outcome measure in stage T1 BCa.…”
Section: Introductionmentioning
confidence: 88%
“…Krajewski et al demonstrated that there is no benefit to reTURB if the procedure is performed eight weeks after the primary TURB and assumed that optimal timing of reTURB is from 2 to 6 weeks after initial TURB. Also, it was shown that each day of reTURB postponement results in a 4% increase in the risk of all analysed clinical events [ 16 ]. Because of this, it might be hypothesized that the time intervals in post-BCG reTURB play a similar role as in conventional reTURB.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients underwent second resection beyond the time frame recommended by the EAU Guidelines and this may result in inferior oncological outcomes [14, 15]. Due to the retrospective study design, specific reasons for delayed reTURBT could not be determined.…”
Section: Discussionmentioning
confidence: 99%